A Case of Insect Colonization Before the Death. Issue 6 (6th March 2017) - Vanin, Stefano; Bonizzoli, Manuela; Migliaccio, Maria Luisa; Buoninsegni, Laura Tadini; Bugelli, Valentina; Pinchi, Vilma; Focardi, Martina
Abstract: Forensic entomology is a branch of forensic science in which insects are used as evidence in legal investigations relating to humans, domestic animals and wildlife. One of the theoretical pillars on which the discipline is based concerns the fact that flies colonize a body after death. However in cases of myiasis, maggots are present before death, with consequences in the correct estimation of the minimum postmortem interval (mPMI). We report here the case of a woman, largely colonized by fly larvae, who has lain alive in her garden for four days prior to being rescued. Larvae were found on the conjunctivae, the bronchi, the rectum and vagina. The woman's death, two months later, was caused by tetanus. The consequences of myiasis on mPMI estimation are here discussed. In fact, despite she was still alive larvae, indicated and estimated age of 1.5–2.5 days, based on environmental and body temperature.